Taxonomic changes in African Stratiomyidae (Diptera) - Hauser, Martin; Woodley, Norman E.; Fachin, Diego A. (Zootaxa, 2017)
Thirteen new generic synonyms, nineteen species synonyms and forty-eight new combinations of African Stratiomyidae are proposed (senior synonym in parentheses):Arthronemina Lindner in James, 1980 syn. nov. (=Argyrobrithes Grünberg, 1915), Arthronema Lindner, 1966b syn. nov. (=Argyrobrithes Grünberg, 1915), Brachyphleps Lindner, 1965 syn. nov. (=Psapharomys Grünberg, 1915), Dinosargus Lindner, 1968 syn. nov. (=Gongrosargus Lindner, 1959), Dolichodema Kertész, 1916 syn. nov. (=Thorasena Macquart, 1838), Gobertina Bigot, 1879a syn. nov. (=Sternobrithes Loew, 1857), Himantochaeta Lindner, 1939 syn. nov. (=Nyplatys Séguy, 1938), Hypoxycera Lindner 1966a syn. nov. (=Hypoceromys Lindner, 1935), Leucacron Lindner, 1966b syn. nov. (=Ptilinoxus Lindner, 1966b), Lonchobrithes Lindner, 1968 syn. nov. (=Argyrobrithes Grünberg, 1915), Meristomeringella Lindner 1965 syn. nov. (=Hypoceromys Lindner, 1935), Physometopon Lindner, 1966b syn. nov. (=Cardopomyia Kertész, 1916), Psapharomydops Lindner, 1966a syn. nov. (=Steleoceromys Grünberg, 1915), Adoxomyia grisea (Séguy, 1931) syn. nov. (=Adoxomyia argenteofasciata (Bezzi, 1906)), Argyrobrithes argenteus Grünberg, 1915 syn. nov. (=Argyrobrithes fuscicornis (Bezzi, 1914)), Argyrobrithes crinitus Lindner, 1972 syn. nov. (=Argyrobrithes zernyi Lindner, 1943), Brachyphleps tristis Lindner, 1965 syn. nov. (=Psapharomys salebrosa Grünberg, 1915), Chrysochroma laetum Lindner, 1966b syn. nov. (=Ptectisargus abditus (Lindner, 1936), Dolichodema africana Kertész, 1916 syn. nov. (=Thorasena pectoralis (Wiedemann, 1838)), Gongrosargus distinguendus Lindner, 1966c syn. nov. (=Gongrosargus glaucus (Bigot, 1859)), Gongrosargus exclamationis Lindner, 1968 syn. nov. (=Gongrosargus pallidus (Macquart, 1838)), Gongrosargus univittatus Lindner, 1966b syn. nov. (=Gongrosargus pallidus (Macquart, 1838)), Hypoxycera simplex Lindner, 1966a syn. nov. (=Hypoceromys jamesi (Lindner, 1965)), Lonchobrithes modestus Lindner, 1968 syn. nov. (=Argyrobrithes curtilamellatum (Lindner, 1966)), Microptecticus clarus Lindner, 1968 syn. nov. (=Microptecticus ambiguus Lindner, 1966b), Neopachygaster umbrifera Lindner, 1966a syn. nov. (=Neopachygaster stigma Lindner, 1938), Odontomyia impressa Curran, 1928 syn. nov. (=Afrodontomyia gigas (Brunetti, 1926)), Odontomyia protrudens Curran, 1928 syn. nov. (=Afrodontomyia erecta (Brunetti, 1926)), Physometopon minor Lindner, 1968 syn. nov. (=Cardopomyia robusta Kertész, 1916), Platyna denudata Grünberg, 1915 syn. nov. (=Platyna hastata (Fabricius, 1805)), Ptectisargus lucidus Lindner, 1968 syn. nov. (=Ptectisargus abditus (Lindner, 1936)); Afrodontomyia erecta (Brunetti, 1926) comb. nov. (from Odontomyia), Afrodontomyia flammiventris (Brunetti, 1926) comb. nov. (from Odontomyia), Afrodontomyia rufiventris (Curran, 1928) comb. nov. (from Stratiomys), Argyrobrithes curtilamellatum (Lindner, 1966b) comb. nov. (from Arthronemina), Argyrobrithes fuscicornis (Bezzi, 1914) comb. nov. (from Sternobrithes), Cardopomyia parvicornis (Lindner, 1959) comb. nov. (from Pseudoxymyia Lindner, 1958), Cardopomyia vesicularis (Lindner, 1966b) comb. nov. (from Physometopon), Cephalochrysa bigoti (Lindner, 1968) comb. nov. (from Chrysochroma), Cephalochrysa flavum (Lindner, 1968) comb. nov. (from Chrysochroma), Cephalochrysa fortunatum (Lindner, 1966b) comb. nov. (from Chrysochroma), Cephalochrysa lapidis (Lindner, 1966b) comb. nov. (from Chrysochroma), Cephalochrysa latum (Lindner, 1966b) comb. nov. (from Chrysochroma), Cephalochrysa lucens (Lindner, 1968) comb. nov. (from Chrysochroma), Cephalochrysa matilei (Lindner, 1979) comb. nov. (from Chrysochroma), Cephalochrysa triste (Lindner, 1966b) comb. nov. (from Chrysochroma), Cephalochrysa turbidum (Lindner, 1965) comb. nov. (from Chrysochroma), Cephalochrysa vadoni (Lindner, 1966b) comb. nov. (from Chrysochroma), Gongrosargus flavipennis (Macquart, 1838) comb. nov. (from Sargus), Gongrosargus lateritius (Lindner, 1968) comb. nov. (from Dinosargus), Gongrosargus limbatus (Macquart, 1838) comb. nov. (from Sargus), Gongrosargus pallidus (Macquart, 1838) comb. nov. (from Sargus), Hypoceromys nigripes (Lindner, 1938) comb. nov. (from Pachygaster), Hypoceromys jamesi (Lindner, 1965) comb. nov. (from Meristomeringella), Microptecticus magnicornis (Lindner, 1936) comb. nov. (from Ptecticus), Microptecticus nigricoxa (Lindner, 1936) comb. nov. (from Microchrysa), Ptecticus lateritius (Rondani, 1863) comb. nov. (from Sargus), Ptectisargus abditus (Lindner, 1936) comb. nov. (from Ptecticus), Ptectisargus brunneus (Lindner, 1936) comb. nov. (from Ptecticus), Ptectisargus cingulatum (Lindner, 1968) comb. nov. (from Chrysochroma), Ptectisargus flavifrons (Lindner, 1968) comb. nov. (from Chrysochroma), Ptectisargus flavomarginatus (Loew, 1857) comb. nov. (from Chrysonotus), Ptectisargus gracilipes (Lindner, 1936) comb. nov. (from Ptecticus), Ptectisargus keiseri (Lindner, 1966b) comb. nov. (from Chrysochroma), Ptectisargus longestylum (Lindner, 1966b) comb. nov. (from Chrysochroma), Ptectisargus punctum (Lindner, 1968) comb. nov. (from Chrysochroma), Ptectisargus ranohira (Woodley, 2001) comb. nov. (from Chrysochroma), Ptectisargus unicolor (Lindner, 1968) comb. nov. (from Chrysochroma), Ptilinoxus interruptum (Lindner, 1966b) comb. nov. (from Leucacron), Sargus congoense (Lindner, 1965) comb. nov. (from Chrysochroma), Sargus flavipes (Lindner, 1966a) comb. nov. (from Chrysochroma), Sargus luctuosus (Lindner, 1938) comb. nov. (from Paraptecticus), Sargus opulentum (Grünberg, 1915) comb. nov. (from Chrysochroma), Sargus pallidiventre (Brunetti, 1926) comb. nov. (from Chrysochroma), Sargus ptecticoideum (Lindner, 1966a) comb. nov. (from Chrysochroma), Steleceromys procera (Lindner, 1966a) comb. nov. (from Psapharomydops), Sternobrithes mercurialis (Lindner, 1938) comb. nov. (from Gobertina), Sternobrithes picticornis (Bigot, 1879b). comb. nov. (from Gobertina), Thorasena pectoralis (Wiedemann, 1824) comb. nov. (from Hermetia), Thorasena fenestrata (James, 1949) comb. nov. (from Dolichodema). One genus was resurrected out of synonymy (Thorasena Macquart, 1838 stat. rev.) and one genus removed from the African fauna (Cyphomyia Wiedemann, 1819).